2022
DOI: 10.3390/agronomy12112897
|View full text |Cite
|
Sign up to set email alerts
|

Influence Evaluation of Enzyme Treatments on Aroma Profile of White Wines

Abstract: Improving aroma profile represents one of the principal goals in winemaking. This paper focuses to evaluate the influence of enzymes applied before alcoholic fermentation of Fetească regală and Sauvignon blanc wines, even if most studies analyze their use in different winemaking stages. Fetească regală wines are described by higher proportions (1.07–4.28%) of ethyl octanoate (exotic fruits), 3-methylbutyl acetate (pear, banana), hexanoic acid (creamy, phenolic, exotic fruits), propan-2-yl acetate (ripe fruits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
3
3
0
Order By: Relevance
“…It was observed that, compared with other Feteasca wines from Romania [52], the three wines had higher content in organic acids, and this is indubitably the terroir influence. However, the obtained values for ester concentration and their type were similar with Feteasca alba and Feteasca regala obtained from grapes harvested from Iași-Copou vineyard, located at 47°10′ north latitude and 27°35′ east longitude (Moldavia region) [53].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…It was observed that, compared with other Feteasca wines from Romania [52], the three wines had higher content in organic acids, and this is indubitably the terroir influence. However, the obtained values for ester concentration and their type were similar with Feteasca alba and Feteasca regala obtained from grapes harvested from Iași-Copou vineyard, located at 47°10′ north latitude and 27°35′ east longitude (Moldavia region) [53].…”
Section: Resultssupporting
confidence: 78%
“…β-citronellol varied from 38 µg/L in Feteasca alba from Aiud and Sarica Niculitel up to 51 µg/L in Feteasca regala from Silagiu (Supplementary Material-Table S1). The present study identified, for the first time, the presence of these terpenoid compounds in Feteasca alba and Feteasca regala white wines, other authors identifying them in Romanian Muscat wines [53].…”
Section: Resultssupporting
confidence: 58%
“…Other authors have previously studied the effect of commercial enzyme preparations on the aroma profile of wine. The influence of five commercial enzyme treatments with pectinolytic and glycosidase activities on volatile compound families, other than terpenes and C13-norisopronodeis, revealed a variable evolution of these compounds during alcoholic fermentation depending on the type of enzymes added [ 28 ]. These authors reported that enzyme treatments increased the volatile compounds compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…These authors reported that enzyme treatments increased the volatile compounds compared to the control. Significant differences in the quality of the final wines were also found, depending on the type of enzyme used [ 28 ]. Enzyme-treated wines with the commercial preparation AR2000, which possesses relevant glucosidases, enhanced the attributes of honey, lime, and smoky and were preferred to the control wines [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of aroma constituents in sparkling wines, with a direct impact on their sensory characteristics, is affected by several factors, for example, the composition of the base wine, grape growing conditions, inoculated yeasts, stage of aging and winemaking practices. The sensory perception of sparkling wines is given by the interaction of different volatile constituents, while its character is influenced by effervescence, sweetness, acidity or bitterness and generated by non-volatile compounds that are soluble in water or a mixture of alcohols [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%